Female foraging impairment related to reproduction in a neotropical spider. Issue 5 (2nd September 2020) - Pollo, Pietro; Spindler, Claudia S.; Costa-Schmidt, Luiz E.
Abstract : Females not only produce costly gametes, but also store the eggs until laying them, a period called gravidity. The volume that eggs occupy in the female abdomen may decrease female foraging ability by making them slower. Although females of all species are subjected to these potential costs, it remains an unexplored matter in invertebrates. Females of the spider Paratrechalea ornata carry their egg sac after oviposition and thus represent a unique opportunity to evaluate gravidity costs because females carry an extra volume before and after laying eggs. We conducted foraging ability experiments using P. ornata females on different treatments regarding gravidity and maternal care. We first hypothesized that internal egg load and egg sac carrying decrease female foraging ability. We also hypothesized that greater egg sac size decreases female foraging ability. We found that both internal egg load and egg sac carrying decreased female foraging ability, and females about to oviposit had a similar foraging ability to females carrying an egg sac. Egg sac size did not influence female foraging ability. Our results show that females' foraging ability changes before the maternal care period and therefore may influence their life-history evolution. The little support for our second hypothesis may also suggest that the decrease in foraging ability is not due to the volume being carried per se, but possibly an associated physiological state.